1960
DOI: 10.1113/jphysiol.1960.sp006482
|View full text |Cite
|
Sign up to set email alerts
|

Actions and interactions of aldosterone monoacetate and neurohypophysial hormones on the isolated cat kidney

Abstract: Intravenous infusions of quantities of aldosterone too small to affect renal function raised the concentration of potassium in the plasma of cats under chloralose anaesthesia (Davey & Lockett, unpublished). This observation indicated extra-renal action of the hormone and raised the question whether the effects of aldosterone on renal function were predoininantly the result of the direct action of this compound within the kidney itself or were, in large part, the consequence of its extra-renal effects. The exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

1961
1961
1994
1994

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 6 publications
1
51
0
Order By: Relevance
“…Both hypophysectomized rats (Table 2) and cat's kidneys perfused with blood from headless or hypophysectomized donor animals (Davey & Lockett, 1960) a-g inclusive caused urinary loss of salt and water, those at h, j and k did not. ACO, anterior commissure; C, cerebellum; CC, corpus callosum; CH, cerebral hemisphere; CQ, corpora quadrigemina; F, fornix; P, pons; PC, posterior commissure; Pi, pineal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both hypophysectomized rats (Table 2) and cat's kidneys perfused with blood from headless or hypophysectomized donor animals (Davey & Lockett, 1960) a-g inclusive caused urinary loss of salt and water, those at h, j and k did not. ACO, anterior commissure; C, cerebellum; CC, corpus callosum; CH, cerebral hemisphere; CQ, corpora quadrigemina; F, fornix; P, pons; PC, posterior commissure; Pi, pineal.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on the isolated perfused kidney of the cat by Davey & Lockett (1960), and de Lima, Lockett & Roberts (1961) have shown that the actions of aldosterone in this preparation differ from those usually observed in intact animals, and are modified by substances derived from the hypophysis. Physiological concentrations of aldosterone have a diuretic naturetic effect on these kidneys when they are being perfused with blood from headless or hypophysectomized donor animals.…”
mentioning
confidence: 99%
“…For example, combined oxytocin and aldosterone produced a much larger increase in Na+ transport in the toad bladder than observed when either of the hormones were added separately (Girardet, Geering, Gaeggler & Rossier, 1986). Davey & Lockett (1960) also proposed that aldosterone interacts with oxytocin to influence renal Na+ handling. The current study was designed to investigate the possibility of such an interaction.…”
Section: Introductionmentioning
confidence: 99%
“…. 1966aDavey and Lockett, 1960) nnder cbloralose anaestbesia. Tbe blood used to fill tbe perfusion eirciiit was collected from male, female or neutered cats wliich were either intact (8 experiments) or in which the brachiocephalic and L-subclavian arteries had been ligatured (headless donors) for 13-21 min.…”
Section: Materials and Nlkniodsmentioning
confidence: 99%